Secure Geographic Routing Hybrid Approach For Void Resolution In Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
- In this paper, we propose a new hybrid approach between the geographic greedy mode and the recovery mode in orderto improve routing efficiency in number of hops, without network overhead. It exploits the optimal topological route to basestations, obtained by beacon messages, as a resource to find better routes than the ones created by greedy mode and recoverymode. We show by simulations that the proposed hybrid approach leads to a significant improvement of routing performancewhen applied to combined greedy and recovery routing algorithms.